The Role of Mature Brain-Derived Neurotrophic Factor and Its Precursor in Predicting Early-Onset Insomnia in Stroke Patients Experiencing Early Neurological Deterioration - Shi G; Yu P; Wang Z; Xu M; Guo M; Wang X; Zhou R (Nature and Science of Sleep)
Guomei Shi,1,2 Peng Yu,2,3 Ziru Wang,2,4 Mingyang Xu,2,3 Minwang Guo,2,3 Xiaorong Wang,2,3 Rujuan Zhou2,3 1Department of Neurology, Taixing Clinical College of Bengbu Medical College, Taixing, Jiangsu, People’s Republic of China; 2Stroke Center, Taixing People’s Hospital, Taixing, Jiangsu, People’s Republic of China; 3Department of Neurology, Taixing People’s Hospital, Taixing, Jiangsu, People’s Republic of China; 4Department of Rehabilitation, Taixing People’s Hospital, Taixing, Jiangsu, People’s Republic of ChinaCorrespondence: Rujuan Zhou, Taixing People’s Hospital, No. 1 Changzheng Road, Taixing, Jiangsu Province, 225400, People’s Republic of China, Tel +86-13951158499, Email zhourujuan123@163.comBackground: The investigation and management of early-onset insomnia (EOI) in patients undergoing early neurological deterioration (END) appear to be insufficiently prioritized in clinical practice. Brain-derived neurotrophic factor (mBDNF) and its precursor, proBDNF, play essential roles in neuroplasticity and may be involved in the pathophysiological mechanisms underlying EOI. This study aimed to investigate the associations of serum mBDNF, proBDNF, and the mBDNF/proBDNF ratio with EOI in stroke patients experiencing END.Methods: In a prospective cohort study from October 2021 to December 2023, 232 stroke patients with END and 56 healthy controls (HCs) were enrolled. Serum levels of mBDNF and proBDNF were quantified using enzyme-linked immunosorbent assays. EOI was diagnosed according to the International Classification of Sleep Disorders, Third Edition (ICSD-3). Patients with END were categorized into subgroups based on the presence or absence EOI.Results: Serum levels of mBDNF, proBDNF, and the mBDNF/proBDNF ratio were significantly lower in END patients compared to those in HCs (all p < 0.05). Among the 232 END patients, 82 (35.3%) developed EOI. Those with EOI had significantly lower levels of mBDNF and the mBDNF/proBDNF ratio compared to those without EOI (all p < 0.001). Multivariate logistic regression analysis revealed that male gender (p = 0.026), Hamilton Depression Rating Scale (HAMD) scores (p < 0.001), mBDNF (p = 0.009), and the mBDNF/proBDNF ratio (p < 0.001) were independent predictors of EOI in END patients. The areas under the curve (AUC) for mBDNF and the mBDNF/proBDNF ratio were 0.686 and 0.778, respectively.Conclusion: Our study identified a correlation between reduced mBDNF levels and a decreased mBDNF/proBDNF ratio with the development of EOI in END patients. In addition, the mBDNF/proBDNF ratio may provide greater insight as a promising biomarker for EOI than mBDNF or proBDNF alone.Keywords: brain-derived neurotrophic factor, ischemic stroke, insomnia, early neurological deterioration, biomarker